Digital communications using frequency - shift keying - Liew Jing Hong, Liew Jing Hong (Universiti Malaysia Sarawak, (UNIMAS), 1998)
Frequency-shift keying (FSK) is one of the digital modulation method used in data communications. It is relatively simple and now mainly used for low-speed data communications, especially in telegraphy. Since the availability of existing vast telephone networks around the world, digital data has been used to modulate analog carrier to produce audible tones for possible transmission over the telephone lines. This function is provided by modems connected at each end of a communications link. This kind of digital modulation is needed to overcome the bandwidth limitation of the telephone lines for original digital data. In this project, XR2206 function generator and RC2211 FSK demodulator integrated circuits (ICs) are to be analysed in terms of their functions in FSK modulation and demodulation. Therefore, an FSK modulator and an FSK demodulator (a functional block in an FSK modem) have been built using the two ICs respectively on two printed circuit boards (PCBs). Then, experiments have been carried out for analysis purposes. The two PCBs have been found to be functioning well and the overall results obtained are satisfactory. There are possible improvements that could be done on this project, and these are suggested for future expansions.